Penyebaran Isu Lingkungan dan Blue and Green Economy (BGE) di Bangkalan Madura - Chotimah Azis, Nur; Muniri, Muniri (Humanist Journal, 2024)
Environmental justice and sustainable development in Indonesia can only be achieved when communities possess adequate understanding of ecological degradation, structural poverty, and social inequality. Madura Island—particularly Bangkalan Regency—exemplifies these challenges, marked by a low Human Development Index and severe environmental issues. This Community Service Project (PKM) aims to strengthen the intellectual and technical capacity of young academic teams in conducting research on environmental issues and the Blue and Green Economy (BGE), while also promoting environmental awareness among the general public, especially youths in Islamic boarding schools (pesantren). Through collaboration with pesantren as community-based educational institutions, the project educates students to think critically about local environmental concerns and raises awareness on the importance of sustainable livelihood choices. It is expected that this initiative will foster a generation of environmentally conscious youth in Madura who adopt greener and more sustainable practices in their socio-economic activities.